TATA KELOLA PERUSAHAAN MENINGKATKAN KINERJA LINGKUNGAN MELALU PERAN PENGUNGKAPAN CRS - Susilo Adi; Agustinus Wardi; Yoto Yoto (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2022)
An unavoidable fact in utilizing the optimization of the company's economic aspects, either directly or indirectly, is the minimization of the impact on environmental conditions. This study seeks to examine empirically to develop models and improve sustainable performance by using various research variables that have been reviewed by various previous researchers. such as corporate governance. The model in the bag at a manufacturing company in Central Java with a composition of 200 samples and data analysis using Amos 25 to obtain inferential statistical results using regression analysis.The results of this study indicate that all hypotheses proposed in this model are accepted and can provide a form of contribution to the development of science related to the acceptance of all hypotheses in the model.Further research in making empirical models based on integration models should add other variables outside of corporate governance and CRS disclosure to improve environmental performance such as corporate social performance, green supply chain management, and institutional pressure. The contribution of the theoretical aspects shown by the development of these findings can contribute to agency theory, and this operational management theory can provide recommendations for managers to improve company performance based on corporate governance.